Enhancing Physics Conceptual Understanding: The Effectiveness of Olabs Media in High School - Hamid, Abdul; Saputri, Mawarni; Nisa, Khairatun; Musdar, Musdar (Universitas PGRI Semarang, 2024)
Olabs, a virtual laboratory, remains underutilized by physics teachers at SMAN 8 Banda Aceh City, despite its potential to enhance students' understanding of physics concepts. This study investigates the effectiveness of Olabs in improving students' concept comprehension. Using a quantitative approach with a quasi-experimental design, 30 students were assessed before and after using Olabs. Results indicate a significant improvement in concept understanding, with an average N-Gain of 0.73, demonstrating the effectiveness of Olabs in physics education.